Development of plasticized methylcellulosepotato starch blend based polymer electrolytes for protonic cell and supercapacitor applications / Muhamad Hafiz Hamsan - Muhamad Hafiz , Hamsan (2020)
In the current work, the preparation of the polymer electrolyte (PE) systems consists of methylcellulose-potato starch polymer matrix, ammonium nitrate (NH4NO3) as ionic source and glycerol as plasticizer are done by solution cast technique. X-ray diffraction (XRD) has shown that blend with 60 wt.% methylcellulose and 40 wt.% potato starch possesses the lowest degree of crystallinity. The possible interactions within the PE are verified using Fourier transform infrared (FTIR) spectroscopy. As the concentration of NH4NO3 is at 30 wt.%, the conductivity is optimized up to (4.37 ± 0.16) × 10-5 S cm-1 and then maximized to (1.26 ± 0.1) × 10−3 S cm−1 with the assist of 40 wt.% glycerol. The conductivity is found to be affected by the ionic mobility (), diffusivity (D) and number density (n). The addition of glycerol has changed the conductivity-temperature relation from Arrhenius to Vogel-Fulcher-Tammann rule. PE in this work is discovered to obey the non-Debye behavior via dielectric study. From transference number measurement (TNM), ions are considered as the dominant charge carrier and the cation transference number (tc) for the highest conducting electrolyte (C4) is 0.40. Thermogravimetric analysis (TGA) portrays thermal stability up to 150 C for the plasticized electrolyte. XRD, differential scanning calorimetry (DSC) and field emission scanning electron microscopy (FESEM) have strengthened the conductivity patterns. C4 is electrochemically stable up to 1.88 V. Galvanostatic charge-discharge measurement of the EDLC has been supported with cyclic voltammetry (CV) analysis. The protonic cells are discharged at various temperatures and constant currents. The rechargeability has been tested at 1 and 4 mA for 15 cycles.